Imaging Features Associated With Failure of Nonoperative Management of Intraabdominal Abscesses in Crohn Disease. Issue 12 (25th April 2019) - Perl, Daniel; Waljee, Akbar K; Bishu, Shrinivas; Higgins, Peter D R; Wasnik, Ashish P; Stidham, Ryan W
Abstract : Management of Crohn's-related intra-abdominal abscesses is challenging. In a retrospective study of patients undergoing non-operative intra-abdominal abscess management, radiographic factors including abscess size, pre-stenotic bowel dilation, and bowel wall thickening are associated with the need for future bowel resection. Abstract: Background: Intraabdominal abscess management decisions in the treatment of Crohn disease (CD) can be challenging. Our aim was to determine the effect of clinical, medication use, and imaging disease characteristics on the need for future surgical management. Methods: A retrospective chart review was performed in patients with CD hospitalized for abscess confirmed by imaging between 2008 and 2016. Selection criteria included nonoperative management with intravenous antibiotics at the index hospitalization and a minimum of 2 years of follow up. Demographic, disease, and medication history were extracted from electronic medical records. Radiographic disease features were assessed by an expert abdominal radiologist, blinded to clinical data. The primary outcome was resection of the bowel segment involving the abscess within 2 years of index hospitalization. Cox proportional hazards regression and statistical methods were performed using SAS 9.4. Results: Of the 121 patients meeting the selection criteria, 36.4% avoided surgery after 2 years of follow up. On adjusted multivariable analysis, disease-activity factors including bowel wall thickness (HR 3.08, 95% CL 1.20–6.21), disease length (HR 2.67, 95% CL 1.40–6.20), bowel dilation (HR 2.19, 95% CL 1.02–4.68), and abscess size of greater than 6 cm (HR 2.47, 95%CL 1.17–5.21) were independent risk factors for future surgery in patients not undergoing immediate bowel resection for abscess management. Biologic use and percutaneous drainage were not risk factors for ultimate surgical management. Conclusions: Radiographic CD features and abscess size over 6 cm are predictors of ultimately requiring bowel resection. Radiographic measures may help stratify patients to immediate surgery or conservative management for intraabdominal CD-related abscesses.